Methods to Identify Strategic Alternatives of Development of the Organization - Juriy Mikhailovich Tsygalov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Modern methodological support of the strategic management of the company offers a wide range of methods to identify possible areas of development of the organization. There are two approaches: marketing for the development of the product, and management, which is based on the improvement of management, decision-making, the development of technology. The starting point for the change strategy of the organization can be regarded as the choice of strategic alternatives of development of the company. A large number of approaches to identify strategic alternatives, creates certain difficulties for their use by researchers. The paper proposes to group the known techniques in three blocks. To simple (1 unit) methods includes such techniques as: identification of strategic alternatives directly by the owners, identification by leadership, quality the conviction of an owner, imposed by choice, by identifying the corporate culture. Easy methods to identify strategic alternatives also include known methods of decision making: brainstorming, scenario development, modeling and other approaches based on expert judgement. To matrix methods (unit 2) include the BCG matrix, the GE/McKinsey&Co, SWOT analysis with 4 active fields, SNW-analysis, STEP (PEST)-analysis, Model ADL - LC, model Fahey and Narayan, the model of stakeholder analysis, the model of M. Porter’s five forces, strategic group maps, model I. Ansoff. Matrix methods do not directly allow to identify strategic alternatives, but represent a simplification of the problem, the disintegration of her to simple situations, allowing you to make informed decisions on the development of a company or a product. Right to identify strategic options to allow graphical and analytical methods, which include the model of M. Porter’s generic strategies, SWOT-analysis 9 active fields, resource model R. Grant and SPACE-analysis. In the context of a specific organization it is necessary to use a combination of the known methods of identification of strategic alternatives, assess options, to negotiate a final choice with owners of the company.